FILMS AND YOUTH: A STUDY TO UNDERSTAND THE IMPACT OF CONTEMPORARY MYTHOLOGICAL HINDI FILMS - Pundir, Sakshi; Mishra, Rashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mythology has always been a significant part of Indian cinema. Technological advancements and filmmakers’ artistic freedom have changed how mythology is presented in Hindi cinema. This exploratory research aims to analyze the influence of contemporary mythology-inspired Hindi films on youths. It also examines the role of Social Networking Sites (SNS) in influencing youth’s interest in mythological films. This paper examines the motivation to explore the Indian epics further among youth as a result of perceiving the incorporation of mythological elements in today’s cinema. To fulfil the objectives, primary data was collected using a random sampling method of 50 respondents who were between the ages of 15 and 45. The survey findings revealed a strong interest and engagement among young people in modern mythological Hindi movies. These films not only provide entertainment but also inspire viewers to explore and connect with their cultural heritage. These films inspire intellectual curiosity and research intent among viewers. Social networking sites play a pivotal role in shaping preferences and understanding of mythological cinema.